Fragmented and Frustrated: The Clamor for Cordillera Regional Autonomy, Philippines - Shivanee A. Dolo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
Regional autonomy is an arrangement used to accommodate a state’s distinct population. This qualitative study investigates the failure to establish regional autonomy in Cordillera, Philippines, despite its inhabitants’ distinct cultural identity and the autonomy provisions of the constitution. It examines the autonomy advocates’ constructions of the clamor’s history and justification. The study outlines the fragmented historical narratives and justifications for the three-decade-long autonomy claim. The historical narratives are divided by the issues of state-sponsored projects in the region and the involvement of communism. Also, additional decision-making powers, economic benefits, and the protection of indigenous peoples’ rights and identity comprise the arguments for its justification. This paper provides an update on the current Cordillera autonomy efforts. It is useful for those interested in the establishment of autonomous regions and how fragmented constructions contribute to its continued frustration.